Comparison of radiographic scoring systems for assessment of bone healing after tibial plateau leveling osteotomy in dogs - Leal, R. A.; Lambrechts, N. E.; Crowley, J. D.; Griffin, J. F.; Karnia, J. J.; Torres, B. T.; Maritato, K. C.; Kieves, N. R.; Duerr, F. M. (Frontiers in Veterinary Science, 2023)
Introduction: Accurate radiographic assessment of bone healing is vital in determining both clinical treatment and for assessing interventions aimed at the promotion of bone healing. Several scoring systems have been used to evaluate osteotomy changes following tibial plateau leveling osteotomy (TPLO). The goal of this study was to compare the ability of five radiographic scoring systems to identify changes in bone healing following TPLO over time (Aim I), and to evaluate the influence of limb positioning on TPLO osteotomy scoring (Aim II). Materials and Methods: Phase I - A randomized, blinded, prospective study was conducted using similarly positioned postoperative TPLO radiographs from seven dogs taken immediately postoperatively, 6-weeks, and 8-weeks postoperatively. Ten reviewers assessed the radiographs, and five different scoring systems were tested for each set including three previously published ones, a Visual Analog Score (VAS), and a subjective 11-point scale. For each system, responses for 6-week postoperative were compared to 8-week postoperative. Scores were judged as correct (=showing an increase in score), incorrect (=decrease in score), or unchanged (=same score). Phase II - An international group of thirty-nine reviewers was asked to score radiographs from three dogs, taken in different positions, using the VAS grading system. Scores were averaged and comparisons were made for each set. Results: Phase I - The VAS system identified the greatest number of sets correctly (76%), with the least unchanged scores (15%), and 9% incorrect scores. Phase II - All three patients had an increase in the average difference between VAS-scores for differently positioned radiographs compared to similarly positioned radiographs. The magnitude of change between different positions far exceeded the magnitude of comparison of the similarly positioned radiographs from the 6- and 8-week time point. Discussion/Conclusion: The VAS system appears to be the most appropriate of the tested systems to identify small changes in bone healing. In addition, the positioning of postoperative TPLO radiographs makes a substantial difference in the healing score that is assigned. Care must be undertaken when performing postoperative radiographs in both the clinical and research setting to ensure accurate assessment of bone healing.